Exploring the Expediency of Waste Materials as Modifiers for Bitumen Mixes - Lukman Olaide Salami; Ifedolapo Omowumi Ameen; Afeez Adefemi Bello (ABUAD Journal of Engineering Research and Development)
This research explores industrial waste materials (waste plastic bottle and waste sachet water) as potentially modifiers for Hot Bitumen Mix (HBM) and Warm Bitumen Mix (WBM). This research becomes necessary because of the poor performance of HBM and WBM. Review of literature revealed that independent use of Waste Plastic Bottle (WPB) and Waste Sachet Water (WSW) significantly enhanced the performance of HBM and WBM. However, literature is scanty on blended use of WPB and WSW. The HBM samples were produced using 60/70 penetration grade of bitumen. Additive (sasobit) was added to the bitumen at 3.5 wt. % of the bitumen for the production of WBM. The HBM and WBM were modified by incorporating blended WPB and WSW thereby forming a composite mixture. The composite was varied at a proportion of 0 – 18 wt. % at 2% interval by 1:1 of the bitumen. The index properties of the HBM and WBM were analyzed. The modified HBM and WBM samples were characterized for microstructure using the X-Ray Fluorescence (XRF). The softening point and penetration index increased with increasing composite mixtures. The penetration reduced with increasing content of the composites. However, the optimum performances were obtained at 10 and 14 wt. % of WPB and WSW for HBM and WBM replacement, respectively, with specific gravity, penetration index, ductility and viscosity of 96, 54, 92, and 75% for HBM and 91, 32, 88, and 89% for WBM, higher than the control mix, respectively. The XRF revealed an enhancement in the adhesion and interlocking in the mineral structure. Exploring WPB and WSW as a modifier for the bitumen mixtures is feasible due to the improved performance of the bitumen mixes. Furthermore, incorporation of the waste materials through their conversion into useful raw materials is an environmental way of waste disposal, and sustainability.